Empowering every voice: Participatory GIS can transform resource management and gender inclusion. Case story of Isiolo County, Kenya - Onyango, Polycarp; Paliwal, Ambica (International Livestock Research Institute, 2024)
In the arid landscapes of Isiolo County in the upper eastern region of Kenya, managing rangeland resources is more than a necessity—it’s the key to survival for the region’s pastoralist communities. But effective resource management requires an understanding that reaches beyond the terrain, one that captures the insights, histories, and wisdom of the people who know these lands best.